The enhanced electrochemical response of Sr(Ti0.3Fe0.7Ru0.07)O3-: δ anodes due to exsolved Ru-Fe nanoparticles - Glaser, R. (2018)
A mixed conducting oxide with a nominal composition Sr(Ti0.3Fe0.7Ru0.07)O3-δ (STFRu) is studied, in comparison with SrTi0.3Fe0.7O3-δ (STF) oxide, as an anode for solid oxide fuel cells. Exposing STFRu to reducing fuel conditions at 800 °C for 4 h results in the exsolution of essentially all of the Ru and a small fraction of the Fe from the oxide, and the formation of Ru1-xFex nanoparticles on the oxide surfaces. Most of the nanoparticles have the hexagonal structure expected for Ru-rich alloys, and thermogravimetric analysis suggests the composition x ∼ 0.2. A small fraction of bcc-structure, presumably Fe-rich, nanoparticles are also detected. Comparison of cells with STFRu and STF anodes shows that the presence of Ru induces a reduced polarization resistance and increases the maximum power density under most cell operating conditions, particularly at lower temperatures and hydrogen partial pressures. For example, at 700 °C and 30% H2 fuel, the maximum power density is 0.1 W cm-2 for STF compared to 0.3 W cm-2 for STFRu. There is also a significant change in the shape of the current-voltage curves and the pH2-dependence of the anode polarization resistances RP,A ∝ (pH2)-m, from m ∼ 0.5-1.0 for STF to m ∼ 0.11-0.29 for STFRu; these suggest that Ru1-xFex nanoparticles improve anode performance by promoting hydrogen adsorption.